Wound Healing in Pediatric Patients with Chronic Skin Wounds: The Critical Role of Nutrition and Nursing Interventions - Alshahrani , Faleh Mubarak; Alzubali, Madkhal Abdulezaz; Alsammak, Amnah Saeed H.; Al Muteri, Muslat Khalaf; Alabyad, Jehan Abdullah Mohammad; Abutaleb, Emad Zaid; Alanazi, Bayan Mohammed Nakthan; Sofyani , Azizah Ahmed; Alshamri , Marzoqa Mashan; Salami, Abdullah Ahmed; Alhamdan, Ali Mohammed; Hassani, Ali Mohammed; et al. (Journal of Ecohumanism, 2024)
Background: Chronic skin wounds, particularly pressure injuries, pose significant challenges in pediatric patients, often resulting from immobility, malnutrition, and other complex health issues. Optimizing nutrition is crucial for promoting healing and maintaining skin integrity in this vulnerable population. Methods: This review analyzes existing literature on the role of nutritional interventions in the management of chronic skin wounds in pediatric patients. A systematic search was conducted using databases such as PubMed, CINAHL, and Embase, focusing on studies published from 2018 to 2023. Key parameters included macro and micronutrient requirements, assessment tools, and multidisciplinary approaches. Results: The findings indicate that adequate nutritional support significantly enhances wound healing in pediatric patients with chronic skin wounds. Macronutrients, particularly protein, are essential for tissue repair, while micronutrients such as zinc and vitamin C play critical roles in immune function and collagen synthesis. The review highlights the importance of individualized nutritional assessments and the integration of registered dietitians in the care team to optimize nutritional strategies tailored to each child's needs. Conclusion: Implementing a structured nutritional management plan is vital for improving outcomes in pediatric patients with chronic skin wounds. Continuous monitoring and adjustment of nutritional intake can enhance healing processes, reduce complications, and improve overall health. Future research should focus on standardized protocols for nutritional interventions and further explore the impact of specific micronutrient supplementation in pediatric wound care.